RESPON PESERTA DIDIK TERHADAP KETERLAKSANAAN PEMBELAJARAN DENGAN MODEL PEMBELAJARAN GUIDED INQUIRY - Gerin Risma Khartaningtyas; Laily Rosdiana (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
The purpose of this research to describe the responses of students in Junior High School toward development of Guided Inquiry on the liquid pressure material. This research uses quantitative descriptive data collection techniques used by questionnaire (questionnaire) after guided inquiry instruction. Respondents were 30 students of class VIII A and 30 students of class VIII B Junior High School of 17 Surabaya. The results showed that all the aspects contained in the student questionnaire responses showed 96% in VIII A with very good category and 90% in VIII B with very good category.